Dietary Patterns, Physical Activity And Obesity Status On Blood Pressure In Hypertensive Patients - Suryani, Tatiek; Syafiq, Ahmad; Sartika, Ratu Ayu Dewi; Putri, Primasti Nuryandari (JKM (Jurnal Kebidanan Malahayati), 2025)
In Indonesia, the prevalence of hypertension has increased significantly, from 25.8% in 2013 to 30.8% in 2023. The proportion of controlled hypertension reached only 19.8% in the productive age group and 17.7% in the elderly. This large number of uncontrolled hypertension cases contributes significantly to the increased risk of cardiovascular disease. The objective of this study was to ascertain the correlation between consumption patterns, physical activity, and obesity status with blood pressure in hypertensive patients in the work area of the Kemirimuka Village Health Center, located in Depok City. This is a quantitative study using a cross-sectional design. The sampling method used was non-probability total sampling, with a sample size of 178 respondents who met the inclusion criteria. The data collected were analyzed univariate and bivariate using the Chi-Square statistical test. The results showed that most of the hypertensive patients, 66.3%, had uncontrolled blood pressure. Statistical test results showed a significant inverse relationship between age and blood pressure (p=0.002 and OR=0.356). In addition, there was a significant relationship between the frequency of junk food consumption and blood pressure (p= 0.017 and OR= 2.269). While the variables gender (p=1.000), frequency of coffee consumption (p=0.154), physical activity (p=0.583), BMI (p=0.594) and BF% (p=0.517) were not associated with blood pressure in hypertensive patients. In conclusion, the elderly group had a 2.81 times lower risk of uncontrolled blood pressure than the productive age group, and frequent consumption of junk food was associated with a 2.269 times increased risk of uncontrolled blood pressure. Education about hypertension, with an emphasis on weight management and healthy eating, should be provided to all age groups. Keywords: Hypertension, Blood pressure, dietary patterns, physical activity, obesity ABSTRACT Di Indonesia prevalensi hipertensi meningkat signifikan, dari 25,8% di tahun 2013 meningkat menjadi 30,8% ditahun 2023. Proporsi hipertensi yang terkendali hanya mencapai 19,8% pada kelompok usia produktif dan 17,7% pada kelompok usia lanjut. Banyaknya jumlah kasus hipertensi yang tidak terkendali ini berkontribusi besar terhadap meningkatnya risiko penyakit kardiovaskular. Tujuan penelitian ini untuk mengetahui hubungan pola konsumsi, aktivitas fisik dan status obesitas dengan tekanan darah pada pasien hipertensi di wilalayah kerja Puskesmas Kelurahan Kemirimuka Kota Depok. Penelitian ini bersifat kuantitatif, dengan menggunakan desain cross-sectional. Metode pengambilan sampel yang digunakan adalah non-probability total sampling, dengan jumlah sampel sebanyak 178 responden yang memenuhi kriteria inklusi. Data yang terkumpul dianalisis secara univariat dan bivariat dengan menggunakan uji statistik Chi-square.  Hasil penelitian menunjukkan bahwa sebagian besar pasien hipertensi 66,3% memiliki tekanan darah tidak terkendali. Hasil analisis menunjukkan hubungan terbalik yang signifikan antara usia dan tekanan darah (p=0.002 and OR=0.356). Selain itu, terdapat hubungan yang signifikan antara frekuensi konsumsi junk food dengan tekanan darah (p= 0.017 and OR= 2.269). Sedangkan variabel jenis kelamin (p=1,000), frekuensi konsumsi kopi (p=0,154), aktivitas fisik (p=0,583), indeks massa tubuh (IMT) (p=0,594) dan persen lemak tubuh (PLT) (p=0,517) tidak berhubungan dengan tekanan darah pada pasien hipertensi. Kesimpulannya, kelompok usia lanjut memiliki risiko 2,81 kali lebih rendah untuk memiliki tekanan darah yang tidak terkontrol dibandingkan kelompok usia produktif, dan seringnya konsumsi junk food ditemukan berhubungan dengan peningkatan risiko 2,269 kali lebih tinggi untuk memiliki tekanan darah yang tidak terkontrol.  Edukasi tentang hipertensi, dengan penekanan pada manajemen berat badan dan pola makan sehat, harus diberikan kepada semua kelompok usia. Kata Kunci: Hipertensi, Tekanan darah, pola makan, aktivitas fisik, obesitas